Efficacy of Live-Attenuated H9N2 Influenza Vaccine Candidates Containing NS1 Truncations against H9N2 Avian Influenza Viruses - Chen, Sujuan; Zhu, Yinbiao; Yang, Da; Yang, Yang; Shi, Shaohua; Qin, Tao; Peng, Daxin; Liu, Xiufan (Frontiers in Microbiology, 2017)
Abstract H9N2 avian influenza virus is a zoonotic agent with a broad host range that can contribute genetic information to H5 or H7N9 subtype viruses, which are significant threats to both humans and birds. Thus, there is a great need for a vaccine to control H9N2 avian influenza. Three mutant viruses of an H9N2 virus A/chicken/Taixing/10/2010 (rTX-NS1-73, rTX-NS1-100, and rTX-NS1-128) were constructed with different NS1 gene truncations and confirmed by western blot analysis. The genetic stability, pathogenicity, transmissibility, and host immune responses towards these mutants were evaluated. The mutant virus rTX-NS1-128 exhibited the most attenuated phenotype and lost transmissibility. The expression levels of interleukin 12 in the nasal and tracheal tissues from chickens immunized with rTX-NS1-128 were significantly upregulated on day 3 post-immunization and the IgA and IgG antibody levels were significantly increased on days 7, 14 and 21 post-immunization when compared to chickens that received an inactivated vaccine. rTX-NS1-128 also protected chickens from challenge by homologous and heterologous H9N2 avian influenza viruses. The results indicate that rTX-NS1-128 can be used as a potential live-attenuated vaccine against H9N2 avian influenza.